Legal status of the Black Sea Cossacks in is administrative-legal system of the Russian empire - Dmytro Bilyi (Cхід, 2013)
In article the author investigates evolution of legal status of the Black Sea Cossack Host in the general administrative and legal system of the Russian empire. The author considers the basic stages of this evolution in a concrete historical context, shows, how depending on concrete historical circumstances legal status of the Black Sea Cossack Host changed. Proceeding from the received results, the author comes to a conclusion that to Cossack elite which has been closely connected with the simple Cossacks, long time was possible to keep as much as possible wide autonomy of the Black Sea Cossack Host, to save up high enough level of democratic traditions of the Ukrainian Cossacks - the self-management, an influential role of Cossack communities, rather considerable economic independence. Thanks to persistence and diplomatic abilities of heads of the Black Sea Cossacks, it was possible to them to achieve from imperial structures of acceptance of such acts which allowed Cossacks of Kuban to keep a wide autonomy that favourably distinguished these Cossacks from other Cossack formations of the Russian empire.